2016
DOI: 10.1371/journal.pone.0166685
|View full text |Cite
|
Sign up to set email alerts
|

Improving Preschoolers’ Arithmetic through Number Magnitude Training: The Impact of Non-Symbolic and Symbolic Training

Abstract: The numerical cognition literature offers two views to explain numerical and arithmetical development. The unique-representation view considers the approximate number system (ANS) to represent the magnitude of both symbolic and non-symbolic numbers and to be the basis of numerical learning. In contrast, the dual-representation view suggests that symbolic and non-symbolic skills rely on different magnitude representations and that it is the ability to build an exact representation of symbolic numbers that under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 70 publications
(89 reference statements)
2
29
1
2
Order By: Relevance
“…Several other studies demonstrated the effectiveness of interventions, games, or curricula in which number lines were used in combination with other training elements, such as magnitude comparison, throwing a die or using a spinner and reading its number, adding numbers before estimating the position of the sum on a number line, or similar (e.g., Fuchs et al., ; Honoré & Noël, ; Thompson & Opfer, ). These studies found positive effects of the interventions on measures of mathematical competence.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies demonstrated the effectiveness of interventions, games, or curricula in which number lines were used in combination with other training elements, such as magnitude comparison, throwing a die or using a spinner and reading its number, adding numbers before estimating the position of the sum on a number line, or similar (e.g., Fuchs et al., ; Honoré & Noël, ; Thompson & Opfer, ). These studies found positive effects of the interventions on measures of mathematical competence.…”
Section: Discussionmentioning
confidence: 99%
“…In the non-numerical control (CTRL) group (adapted from Honoré & Noël, 2016), stories of approximately 20 min were read to the children (a different story in each of the three training sessions). The meaning of three difficult words was explained in the context of each story: ''dune" (dune), ''mirage" (mirage), and ''chèche" (chech) in the first story; ''montagnard" (mountain dweller), ''baluchon" (bundle), and ''brise" (breeze) in the second story; and ''picorer" (to peck), ''miauler" (to meow), and ''avoir la frousse" (expression to say to be scared) in the third story.…”
Section: Trainingmentioning
confidence: 99%
“…First, we used a computerized task developed by Honoré and Noël (2016), the multiple-choice (MC) addition task. The screen was divided into two sections.…”
Section: If It Jumps Three Times It Does 'One -Two -Three' and If It mentioning
confidence: 99%